Deep Vein Thrombosis Secondary To Graves’ Disease-A Case Report - Islam, Md Aminul; Beg, Ayesha; Ahmed, Md Sultan; Chowdhury, Sayed; Haque, Mirza Manjurul (Community Based Medical Journal, 2016)
Deep Vein thrombosis (DVT) is the formation of a blood clot within a deep vein, most commonly the legs. The incidence of a first venous thrombosis is 1-3 per 1000 persons per year, around two-thirds manifest as DVT of the leg, and one-third as pulmonary embolism (PE). Graves' disease, also known as toxic diffuse goiter, is an autoimmune disease that affects the thyroid which frequently results in and is the most common cause of hyperthyroidism, often results in an enlarged thyroid. The disorder results from an antibody, called thyroid stimulating immunoglobulin (TSI), that has a similar effect to thyroid stimulating hormone (TSH) which cause the thyroid gland to produce excess thyroid hormone. Graves' disease will develop in about 0.5% of males and 3% of females, approximately 7.5 times more often in women than men. Various changes in the coagulation- fibrinolytic system have been described in patients with an excess thyroid hormones particularly procoagulant and antifibrinolytic effects. Review analysis confirmed that clinically overt hyperthyroidism modify the coagulation-fibrinolytic balance, indicating that thyroid hormone excess is the probable main pathophysiological mechanism. Patients with overt hyperthyroidism appear to have an increased risk of thrombosis. Here we present a case of right sided leg swelling due to deep vein thrombosis with Grave's disease A 30 year old lady admitted in tertiary care hospital with right sided leg swelling for 25 days and protrusion of both eyes for 3 months. Swelling was sudden in onset, painful, red in colour, which involved almost whole right lower limb and it was associated with venous engorgement. Physical examination revealed patient was ill looking, mildly anaemic, tachycardic, normotensive, severe pitting edema on right leg but left was normal. Thyroid gland was diffusely enlarged. She had bilateral exopthalmos with presence of lid retraction and lid lag. Examination of Lower limbs revealed swollen whole right lower limb with engorged veins in the upper part of thigh with raised local temperature, calf muscle tenderness and positive Homan's sign on right side. The purpose of this case report is to establish that Graves' disease is the cause of DVT in this patient. CBMJ 2016 January: Vol. 05 No. 01 P: 33-41